Do FDI Firms Employ More Workers than Domestic Firms for Each Dollar of Assets? - Ando, Sakai (IMF Working Papers; Working Paper ;, 2020)
This paper studies whether FDI firms employ more workers than domestic firms for each dollar of assets. Using the Orbis database and its ownership structure information, we show that, in most economies, domestic firms tend to employ more workers per asset than FDI firms. The result remains robust across individual industries in the case study of the United Kingdom. The analysis of the switchers (ownership changes from domestic to foreign or vice versa) suggests that ownership changes do not have an immediate impact on the employment per asset. This result suggests that different patterns of employment per asset seem to come from technological differences rather than from different ownership structures.